1974
DOI: 10.1172/jci107605
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Vasodilator Responses to K+ in Essential Hypertensive Men

Abstract: A B S T R A C T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…For example, uncomplicated essential hypertensive patients show attenuated vasodilator/ responses to intraarterial infusion of potassium, suggesting suppressed vascular Na + -pump activity. 31 This form of hypertension is not accompanied by volume expansion, on the contrary, most investigators report decreased plasma volume in such patients. 32 -33 Moreover.…”
Section: Discussionmentioning
confidence: 97%
“…For example, uncomplicated essential hypertensive patients show attenuated vasodilator/ responses to intraarterial infusion of potassium, suggesting suppressed vascular Na + -pump activity. 31 This form of hypertension is not accompanied by volume expansion, on the contrary, most investigators report decreased plasma volume in such patients. 32 -33 Moreover.…”
Section: Discussionmentioning
confidence: 97%
“…Other evidence suggests that decreases in pump activity are not unique to volumeexpanded forms of hypertension. Overbeck et al 2 found attenuated vasodilatory responses to intraarterial infusions of K + in a significant proportion of patients with uncomplicated essential hypertension. There is little evidence that uncomplicated essential hypertension is accompanied by volume expansion; most investigators report that decreased plasma volume characterizes such patients.…”
Section: Discussionmentioning
confidence: 99%
“…KC1 has been reported to have both direct and indirect effects on the vascular system. 32 - 33 Intraarterial infusion of KC1 is known to cause arterial vaso- VOL 6, No 2, MARCH-APRIL 1984 dilation, the degree of which is reduced by pretreatment with ouabain. 32 This observation led Overbeck and others 33 to speculate that there might be a defect in Na, K-ATPase in vascular smooth muscle in some patients with essential hypertension whose K vasodilation was attenuated, and that an increase in plasma K would stimulate the Na-K pump, leading to a reduction in blood pressure by vasodilation.…”
Section: Discussionmentioning
confidence: 99%